A Selection Flowchart for Micromodel Experiments Based on Computational Fluid Dynamic Simulations of Surfactant Flooding in Enhanced Oil Recovery - Santiago Céspedes (MDPI AG, 2021)
A selection flowchart that assists, through Computational Fluid Dynamics (CFD) simulations, the design of microfluidic experiments used to distinguish the performance in Chemical Enhanced Oil Recovery (CEOR) of two surfactants with very similar values of interfacial tension (IFT) was proposed and its use demonstrated. The selection flowchart first proposes an experimental design for certain modified variables (<semantics><mover accent="true">X→</mover></semantics>: porosity, grain shape, the presence of preferential flowing channels, and injection velocity). Experiments are then performed through CFD simulations to obtain a set of response variables (<semantics><mover accent="true">Y→</mover></semantics>: recovery factor, breakthrough time, the fractal dimension of flow pattern, pressure drop, and entrapment effect). A sensitivity analysis of <semantics><mover accent="true">Y→</mover></semantics> regarding the differences in the interfacial tension (IFT) can indicate the CFD experiments that could have more success when distinguishing between two surfactants with similar IFTs (0.037 mN/m and 0.045 mN/m). In the range of modifiable variables evaluated in this study (porosity values of 0.5 and 0.7, circular and irregular grain shape, with and without preferential flowing channel, injection velocities of 10 ft/day and 30 ft/day), the entrapment effect is the response variable that is most affected by changes in IFT. The response of the recovery factor and the breakthrough time was also significant, while the fractal dimension of the flow and the pressure drop had the lowest sensitivity to different IFTs. The experimental conditions that rendered the highest sensitivity to changes in IFT were a low porosity (0.5) and a high injection flow (30 ft/day). The response to the presence of preferential channels and the pore shape was negligible. The approach developed in this research facilitates, through CFD simulations, the study of CEOR processes with microfluidic devices. It reduces the number of experiments and increases the probability of their success.